2010
DOI: 10.1142/s1363919610002829
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Horizons: Leveraging Cross-Industry Innovation Search in the Front-End of the Innovation Process

Abstract: Open innovation" and "external search" for new ideas are central topics in the recent discourse in innovation research. External search helps firms to identify new opportunities for innovation and alleviates the risks of local search. It is widely acknowledged that novel ideas regularly emerge from the combination of distant pieces of knowledge and interaction with "idea suppliers" from distant knowledge domains. However, the current discussion on open innovation has hardly touched upon the question of how fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…By means of R&D internationalization, REs and EEs have opportunities to acquire diversified and complementary knowledge as well as other R&D resources in the external space [41], which may lead to a high level of green innovation. Second, R&D internationalization helps REs and EEs participate in the richness of ties and networks maintained by other enterprises [42][43][44] and interact with a large number of organizations within those networks. Those ties and networks can serve as an importation source such that teams import ideas or relevant information from contacts outside of the team into the team domain [45][46][47].…”
Section: Randd Internationalization and Green Innovationmentioning
confidence: 99%
“…By means of R&D internationalization, REs and EEs have opportunities to acquire diversified and complementary knowledge as well as other R&D resources in the external space [41], which may lead to a high level of green innovation. Second, R&D internationalization helps REs and EEs participate in the richness of ties and networks maintained by other enterprises [42][43][44] and interact with a large number of organizations within those networks. Those ties and networks can serve as an importation source such that teams import ideas or relevant information from contacts outside of the team into the team domain [45][46][47].…”
Section: Randd Internationalization and Green Innovationmentioning
confidence: 99%
“…While many anecdotic examples of cross-industry innovation (Herstatt and Engel, 2006;Gassmann et al, 2010) were reported, only first insights on the cross-industry process itself exist (Herstatt and Engel, 2006;Gassmann and Zeschky, 2008;Brunswicker and Hutschek, 2010). Moreover, there are first hints on the outcome of cross-industry innovation such as helping to cut development costs and speeding up the process of NPD (Kalogerakis et al, 2010).…”
Section: Cross-industry Innovationmentioning
confidence: 99%
“…Moreover, external knowledge may help overcome a firm's inner competency traps (Levinthal and March, 1993) which might especially be relevant for industries with rapid technological developments (Powell et al, 1996) or in a rapidly changing environment (Wang and Chen, 2009). Cross-industry innovation is a specific framework (Brunswicker and Hutschek, 2010) under the open innovation umbrella for accessing external sources from outside a firm's own value chain. It focuses on transferring knowledge from a foreign industry to a firm's own context in order to solve creative problem-solving tasks and to develop innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the open teams might try to increase their information-processing capacity by exploring and assimilating information and knowledge externally (Brunswicker and Hutschek, 2010;Chang et al, 2012), and to share the information-processing burden by co-developing new products or services with external partners (Ettlie and Pavlou, 2006;Tsou and Chen, 2012). Furthermore, we also found that in open cases, customers were involved early.…”
Section: Discussionmentioning
confidence: 74%
“…Firstly, to acquire and assimilate ideas and knowledge from external sources (Chang et al, 2012;Chiang and Hung, 2010) and, secondly, to co-develop with external partners, such as suppliers, customers, competitors, universities, firms in other industries etc. (Brunswicker and Hutschek, 2010;Fey and Birkinshaw, 2005;Oliveira and von Hippel, 2011;Ordanini and Parasuraman, 2011). This is termed as "inbound openness" by Chesbrough (2003), who argues that openness underlies innovation success by allowing the innovating firms to lower R&D cost, increase innovation productivity and newness, and reduce time to market (Chesbrough, 2003;Enkel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%